2023
DOI: 10.1038/s41467-023-36630-w
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction of cysteine and methionine sensitizes gliomas to ferroptosis and induces alterations in energetic metabolism

Abstract: Ferroptosis is mediated by lipid peroxidation of phospholipids containing polyunsaturated fatty acyl moieties. Glutathione, the key cellular antioxidant capable of inhibiting lipid peroxidation via the activity of the enzyme glutathione peroxidase 4 (GPX-4), is generated directly from the sulfur-containing amino acid cysteine, and indirectly from methionine via the transsulfuration pathway. Herein we show that cysteine and methionine deprivation (CMD) can synergize with the GPX4 inhibitor RSL3 to increase ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Gene expression analysis by qRT-qPCR confirmed that cystine deprivation led to the upregulation of targets associated with a ferroptotic response, especially CHAC1, PTGS2, ATF4, and the cystine transporter SLC7A11 (Figure 2a) (Upadhyayula et al, 2023). Next, we sought to understand whether the behavior of MIT/TFE factors in melanoma was altered upon induction of ferroptosis and whether their canonical target genes involved in lysosomal biogenesis would be affected.…”
Section: E T T E R T O T H E E D I T O R Tfe3 Promotes Ferroptosis In...mentioning
confidence: 98%
“…Gene expression analysis by qRT-qPCR confirmed that cystine deprivation led to the upregulation of targets associated with a ferroptotic response, especially CHAC1, PTGS2, ATF4, and the cystine transporter SLC7A11 (Figure 2a) (Upadhyayula et al, 2023). Next, we sought to understand whether the behavior of MIT/TFE factors in melanoma was altered upon induction of ferroptosis and whether their canonical target genes involved in lysosomal biogenesis would be affected.…”
Section: E T T E R T O T H E E D I T O R Tfe3 Promotes Ferroptosis In...mentioning
confidence: 98%
“…a) Left: Schematic of in vivo head-fixed two-photon imaging with simultaneous whisker stimulation. Right: Schematic of tumor injection placement (yellow marker) with respect to somatosensory cortex (green area, modified from Kirkcaldie et al 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in mTOR signaling have been implicated in a variety of neurological diseases with pathological mechanisms relating to mTOR’s critical role in local protein synthesis, dendritic spine morphogenesis and synaptic plasticity 72–74 . Inhibiting mTOR can reduce seizures in animal models of TSC-related epilepsy 75,76 and can reverse TSC-associated alterations in synaptic plasticity with improvements in cognitive deficits 77 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, Met restriction can reduce Cys and GSH (Glu-Cys-Gly) levels, which may lead to the accumulation of cytotoxic concentrations of ROS in cancer cells. Accordingly, evidence has suggested that Cys supplementation can reduce the anticancer activity of Met restriction [131,132], and many studies have restricted or eliminated Cys in the diet to increase the anticancer activity of this Met restriction [26,27,34,40,111,113,[120][121][122]133]. It has been proposed that cancer cells are more vulnerable than normal cells to Met restriction because cancer cells may be unable to recycle Met from homocysteine (HCys) or SAM through the Met salvage pathways [24].…”
Section: Orillion Et Al 2018 [34]mentioning
confidence: 99%